2020
DOI: 10.1007/s10067-020-05353-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlates of small airway obstruction in patients with systemic sclerosis

Abstract: Objectives This study aims to assess the prevalence and clinical correlates of small airway obstruction (SAO) in patients with systemic sclerosis (SSc). Methods Sixty-nine consecutive patients with SSc (63 women and 6 men) were included. Lung function tests, including assessment of lung diffusing capacity, were performed in all patients. Patients were considered to have SAO when the maximal expiratory flow at 25% of the forced vital capacity (MEF 25 ) was lower than 60% as predicted. High-resolution computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Interestingly, we observed that three-fourths of the patients had altered IOS, and more than two-thirds had SAD diagnosed by an increase in R4-R20. In line with our findings, Ostojic and Vujovic [ 5 ] detected SAD in 66.6% of patients with scleroderma, although they used the maximal expiratory flow at 25% of the forced vital capacity to diagnose SAD. Unlike these studies, Bonifazi et al [ 7 ] used IOS and Silva et al [ 22 ] used the nitrogen single-breath washout test and observed SAD in 21.5% and 28.8% of patients with scleroderma, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, we observed that three-fourths of the patients had altered IOS, and more than two-thirds had SAD diagnosed by an increase in R4-R20. In line with our findings, Ostojic and Vujovic [ 5 ] detected SAD in 66.6% of patients with scleroderma, although they used the maximal expiratory flow at 25% of the forced vital capacity to diagnose SAD. Unlike these studies, Bonifazi et al [ 7 ] used IOS and Silva et al [ 22 ] used the nitrogen single-breath washout test and observed SAD in 21.5% and 28.8% of patients with scleroderma, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike these studies, Bonifazi et al [ 7 ] used IOS and Silva et al [ 22 ] used the nitrogen single-breath washout test and observed SAD in 21.5% and 28.8% of patients with scleroderma, respectively. These differences may be explained at least in part by the varied frequencies of interstitial involvement, as SAD may indicate possible prominent bronchiolar involvement in scleroderma-related ILD [ 5 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 69 patients were included in that study and the authors did not perform multivariable analyses to evaluate the associations between SAD and clinical features of SSc. 23 Our findings complement that study by demonstrating that SAD in SSc is both prevalent and associated with common comorbid conditions in these patients.…”
Section: Discussionsupporting
confidence: 85%
“…In the recent years growing interest has focused on the involvement of small airway in various bronchiolar and interstitial lung diseases [18][19][20][21]. Previous studies have found histopathological evidence for SAD in patients with IPF.…”
Section: Discussionmentioning
confidence: 99%